The Indonesian Government’s Incapable Reliance on Private Islamic School Owners in Upholding The Nation’s Principles - Nur kholis (Islamic Studies Journal for Social Transformation, 2022)
This article examines the role of private Islamic schools in Indonesia in providing education and fostering religiousvalues among their students. It argues that the Indonesian government has failed to ensure equal access to qualityeducation for all citizens and to instill a strong sense of religious identity in them. The objective of the article is tohighlight the strategies employed by private Islamic schools in building students' religious character, which is seen asan essential component of their education. The article adopts a qualitative method with a multiple-case study approachon three private Islamic schools in Pekalongan, a city known for its Islamic culture and tradition. The articleidentifies three main strategies that the school foundation management uses to nurture students' religious character:daily supervision, monthly guidance session, and warm personal communication. The article concludes with arecommendation that the government should recognize and support the contribution of